RADIATION OF PATIENTS IN RADIATION THERAPY - Abduvokhidov Shamsiddin Jaloliddin coals; Mamajonova Shohista Mukhtor kizi; Abdukadirova Lola Kabulovna (Journal Park Publishing, 2025)
The problem of regulating medical workers' exposure to radiation has its own peculiarities. It is necessary to keep in mind that medical radiation is a powerful anthropogenic factor, causing 15-30% of the population dose [2], however, in radiation therapy, as in other medical exposures, the most important principle formed by the ICRP is at work: the benefit from radiation should be greater than the harm in the absence of radiation. Nevertheless, the maximum possible reduction of the dose without compromising the desired effect is important for both the patient and the staff.